2008
DOI: 10.1111/j.1365-2109.2008.02041.x
|View full text |Cite
|
Sign up to set email alerts
|

Seminal plasma composition and its relationship with physical spermatological parameters of Grass carp (Ctenopharyngodon idella) semen: with emphasis on sperm motility

Abstract: In this research, the mineral and organic composition of the seminal plasma, physical spermatological parameters and their physiological relationships were investigated in grass carp (Ctenopharyngodon idella). The seminal plasma contained 98.14 AE 5.23 mM L À 1 (Na 1 ), 380.85 AE 25.95 mM L À 1 (K 1 ), 30.25 AE 4.96 mg dL À 1 (Ca 21 ), 19.16 AE 1.70 mEq L À 1 (Mg 21 ), 1.36 AE 0.11mg dL À 1 glucose, 0.37 AE 0.08 g dL À 1 total protein,12.02 AE 1.18 mg dL À 1 cholesterol,14.85 AE 1.50 mg dL À 1 triglyceride and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 28 publications
3
26
1
1
Order By: Relevance
“…The highest mean spermatozoa density (33.914 ±157.59 x10 9 mL -1 ) in the present study was higher than the results reported by Bozkurt et al (2008) for grass carp (15.43±0.72) and Akcay et al (2004) for mirror carp (17.33±1.22 x10 9 mL -1 ). The differences may be due to differences in feeding conditions, age, environmental factors (such as day length and temperature), time of spawning, or dilution ratio.…”
Section: Evaluation Of Fertilization Successcontrasting
confidence: 57%
See 1 more Smart Citation
“…The highest mean spermatozoa density (33.914 ±157.59 x10 9 mL -1 ) in the present study was higher than the results reported by Bozkurt et al (2008) for grass carp (15.43±0.72) and Akcay et al (2004) for mirror carp (17.33±1.22 x10 9 mL -1 ). The differences may be due to differences in feeding conditions, age, environmental factors (such as day length and temperature), time of spawning, or dilution ratio.…”
Section: Evaluation Of Fertilization Successcontrasting
confidence: 57%
“…Mean sperm volume is in the range of findings of Belova (1981) that indicates the range as 1-9 ml during spawning season. On the other hand, the highest mean sperm volume (8.20±3.23) was lower than that of Bozkurt et al (2008) for grass carp (14.44±1.16 ml). The differences may be due to differences in age, environmental factors (such as water temperature etc.)…”
Section: Evaluation Of Fertilization Successmentioning
confidence: 84%
“…There is insufficient information about the role of cholesterol in seminal plasma in spite of its identification in the seminal plasma of freshwater fish (Billard et al, 1995). Lipids and cholesterol may have a protective effect against environmental changes (especially in temperature) that occurs when the fish semen is released (Bozkurt et al, 2008b). Another interesting point is the lack of glucose in seminal plasma.…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that the K + ion at certain concentrations also tends to inhibit the Salmo trutta macrostigma spermatozoa since a negative allometry was determined between K + and motility. The seminal plasma of Salmo trutta macrostigma has a higher Na + content (121.0 ± 0.37mM/l) than rainbow trout (80 mmol/l; Secer et al, 2004) and grass carp (98 mmol/l; Bozkurt et al, 2008b) but lower than other freshwater species such as perch (124 mmol/l; Lahnsteiner et al, 1995), Asian catfish (164 mmol/l; Tan-Fermin et al, 1999), and muskellunge (129 mmol/l; Lin et al, 1996). It is interesting to note that there is also a negative interaction between Na + and motility (P > 0.05) in spite of the higher Na + level than that reported for the rainbow trout .…”
Section: Discussionmentioning
confidence: 99%
“…Sperm was kept on ice and immediately transported to the laboratory for analyses. According to procedure of Bozkurt et al (2008) sperm motility was triggered directly in activation medium of 0.3% NaCl at ratio 1 : 1000 and immediately recorded with a 3 CCD video camera Panasonic WV-CP240 (Panasonic Corp., Osaka, Japan) mounted on a dark-field microscope (Leica Camera, Allendale, USA). The duration of sperm motility was measured immediately after initiation of sperm activation until 100% of the spermatozoa were immotile.…”
Section: Methodsmentioning
confidence: 99%